(untitled) (European Journal of Behavioral Sciences, 2020)
Social networks are an integral part of our everyday lives, becoming an indispensable medium for communication in personal and business environment. New forms and ways of communication change the general mind set and significantly affect the quality of life of individuals. Quality of life is perceived as an abstract term, but often people are not aware that they directly affect the quality of their own lives, making minor but significant everyday choices and decisions. Quality of life can be defined broadly but in the widest sense it involves a subjective sense of satisfaction with one’s life. Scientific knowledge about the impact of social networks on self-assessment of the quality of life of individuals is only just beginning to be researched. Available research indicates potential benefits as well as a number of disadvantages. In the context of the previous claims, the focus of the study conducted by the authors of this paper focuses on analysing the impact of social networks on individual’s self-assessment of quality of life and the correlation between time spent on social networks, and the choice of content that individuals choose to share to present themselves. Moreover, it is aimed to explain how much and in what ways they critically judge the lives of others online. The research aspires to show the positive as well as negative aspects that social networks, primarily Facebook and Instagram, have on creating a picture of individuals and how they compare themselves with others. The topic of this paper is based on quantitative research conducted on a representative sample. An analysis of the results of the survey conducted online has elaborated a hypothesis which claims that content shared by individuals on social networks influences the image they create about themselves. A comparative analysis of the results obtained with the results of similar research has led to the conclusion about the synergistic influence of social networks on the feeling of the quality of life of respondents. The originality of this work is reflected in the approach of conducting research by examining attitudes about an individual’s life satisfaction, the way he or she creates a picture of himself/herself through social networks, the extent to which he/she compares herself/himself with others, and what social media applications he/she uses. At the cognitive level, scientific contributions were made through the development of information concepts on quality of life, and at the methodological level through the development of an original methodology for qualitative alignment of respondents’ attitudes using statistical analysis. Furthermore, at the practical level through the application of concepts in assessing the creation of self-image and the image of others through social networks.